What Would Your Organisation Like to Be the First Tangible Output From CCAFS? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Jon Padgham, Program Director at START (global change SysTem for Analysis, Research and Training). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya